HUBUNGAN KEMAMPUAN MATEMATIKA DENGAN POTENSI AKADEMIK MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA IKIP PGRI PONTIANAK - Ardiawan, Yadi; Nurmaningsih, Nurmaningsih (JURNAL e-DuMath, 2017)
Abstract: This study aims to examine the relationship between math skills with the academic potential of students IKIP PGRI Pontianak. This study is correlational research design bivariate correlation. The population in the study were all students of Mathematics Education Semester IV consists of four study groups (classes) that two morning classes (A and B) and two afternoon classes (A and B). With purposive sampling technique was chosen as a class A sample. Based on the results obtained by regression analysis using SPSS t value of 0.379 and a significance of 0.707 > 0.01, which means that H0 accepted. Thus we can conclude there is no significant relationship between mathematical skills with academic potential of students IKIP PGRI Pontianak.Keywords: relationship , math skills , academic potential.